Review of the Cyana rejecta (Walker, 1854) species-group, with descriptions of three new species from mainland Africa and a new subspecies from Madagascar (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V.; László, Gyula M. (Zootaxa, 2020)
The present paper provides an overview of the Cyana rejecta (Walker, 1854) species-group. Three new species (C. yao sp. n., C. occidentalis sp. n. and C. cornutissima sp. n.) and a new subspecies (C. rejecta viettei ssp. n.) are described. Adults, male and female genitalia of all taxa of the species-group are illustrated.